Not Just Fat: Imaging in Abdominal Fat Pathology - Patil, Aruna R.; Nandikoor, Shrivalli; Jagannath, Pramod; Bansal, Amit (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Fat in abdomen has diverse distribution and function. Insult to fat due to several causes can result in infarction or necrosis and present as acute abdomen clinically. Intra-abdominal focal fat infarction is one such condition that comprises of epiploic appendagitis, perigastric appendagitis, omental infarction, and torsion of fatty appendage of falciform ligament that have characteristic imaging features. Secondary causes of fat necrosis include pancreatitis or trauma related. Metabolic or responsive fat changes, like hypertrophy and dystrophy, can be diagnosed on imaging especially on computed tomography. Mesentric fat stranding including the mesentric panniculitis spectrum poses diagnostic dilemma and the causes and imaging role are covered in this review. Some infections and neoplasms that preferably affect abdominal fat compartments may mimic benign conditions, although some have specific patterns of involvement.
Keywords: omentum; computed tomography; ultrasonography; infarction; appendagitis